Acute psychosis in glycogen storage disease: a rare but severe complication. Issue 7 (4th July 2019) - Dunne, Thomas Frederick; Geberhiwot, Tarekegn; Jones, Rowena
Abstract : Glycogen storage disease type 1 (GSD-1) is a group of inherited metabolic disorders characterised by the inability to use intracellular glucose stores. It is associated with a high risk of hypoglycaemia, as well as long-term complications including growth retardation, hepatocellular adenomas, renal disease, hypertriglyceridaemia and hyperuricaemia. Treatment involves slow absorption carbohydrates, for example, cornstarch. We present a case of acute psychosis in a patient with GSD-1a. This was initially attributed to his opiate use. Later in his management an MRI scan of his head was performed which revealed regions of brain atrophy following significant hypoglycaemic insult, thus identifying an organic cause of his psychosis. This case presents a rare complication of glycogen storage disease: organic psychosis attributable to cortical atrophy from profound hypoglycaemic insult. It emphasises the importance of investigating organic causes of psychiatric symptoms.